Preparation and characterization of physical properties of Durian skin fibers biocomposite - Manshor, R.M; Anuar, Hazleen; Wan Busu, Wan Nazri; M.I, Ahmad Fitrie (Trans Tech Publications, Switzerland, 2012)
Durian skin fibres (DSF) are cellulose-based fibres extracted from the durian peel. This paper present the physical behaviour, chemical structure and crystallinity of the fibres, as observed by environmental scanning electron microscope (ESEM), Fourier transform infrared (FTIR) and Xray diffraction (XRD). The characteristic of the natural fibers produces from durian skins are similar with other types of natural fiber. The average diameter and density are 0.299 mm and 1.243 g/cm3, respectively while the crystallinity index is slightly higher than the common fibers. The properties and charecteristic of durian skin fibers are within the propertise of lignocellulosic fiber which is suitable for development of biocomposite materials.